Implementasi Modul Monitoring Kapasitas Baterai Pada Perangkat Embedded - Yohana Kristinawati; Sabriansyah Rizqika Akbar; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
ABSTRACT Nowadays. the topic about energy scarcity issue becomes quite often discussed in the development of modern technologies such as wireless sensor network (WSN). From many of its implementations. WSN's main problem is about energy consumption. This is happened because the power supply of the node only supplied by a battery for its operation, so it has limited energy reserves. If one node dies, it will change the network performance in terms of routing and topology. In this study, a battery capacity measurement module is implemented on an embedded device. If the battery capacity information of the battery is known, then the approximate time of how long the embedded device can continue running will also be know, and so it can support the further development of energy savings on embedded devices. In its implementation. the module uses a resistor shuntto obtain a the value of drop voltage which is then can be used to measure the current flowing on an embedded device using Ohm's Law. When the current is known. the battery capacity can be calculated. Value processing is done by using arduino nano microcontroller. The module then provides battery capacity information in the form of percent value and the current flow value on the embedded device via LCD. It is concluded that the module can measure the current flow of the embedded device and the module can also calculates the battery capacity that used by the embedded device. The module works with a 94,56% accuracy level in measuring battery capacity.